Hambatan Belajar Membaca Peserta Didik Sekolah Dasar pada Anak TKW di Daerah Kabupaten Bima - Agustina, Anggita (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Reading is a process carried out by students in understanding the content in reading books so that students know things that will be explained by educators from reading books. The factors that hinder students' learning to read are internal factors which include lack of student motivation, lack of student interest in reading, students have difficulty putting words together into sentences, students often do not attend school. Meanwhile, the external factors are lack of support and motivation by father and mother, lack of interaction, no facilities provided for students studying at home, and no direct guidance from parents because the mother is a migrant worker so the child lives with the father and foster parents. which makes children careless and undirected. This research aims to determine the factors inhibiting students' learning to read, teacher strategies, and parenting patterns among TKW parents at SDN Inpres 1 Simpasai. This research uses descriptive qualitative. Data collection techniques include observation, interviews, field notes with teachers, students and parents as informants. The data analysis technique uses instrument extension, peer discussion, checking the validity of the data, then drawing conclusions.